2011
DOI: 10.1063/1.3667134
|View full text |Cite
|
Sign up to set email alerts
|

Engineering titanium and aluminum oxide composites using atomic layer deposition

Abstract: Mixed metal oxides provide a convenient means to produce coatings with tailored physical properties. We investigate the possibility of synthesizing novel coatings of mixed titanium and aluminum oxide using atomic layer deposition (ALD). Results show that ALD films were prepared with compositions ranging between Al2O3 and TiO2 having refractive indices between 1.6 and 2.4 (at λ = 550 nm) at low temperature. The microstructure and bonding environment within the films was investigated using electron microscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This structure cannot be upheld in a bulk crystal. In accordance with the TiO 2 -free reference Al 2 O 3 sample of ref , it is therefore concluded that all ALD-Al 2 O 3 -based films, i.e., pure films and monolayers sandwiched between SiO 2 , have only a tetrahedral O coordination. This is supported by molecular dynamics structure studies of amorphous Al 2 O 3 that calculated 85% 4-fold coordination (plus 13% 5-fold coordination) for densities of 3.0 g/cm 3 , a typical value for ALD-Al 2 O 3 deposited at elevated temperatures. , …”
Section: Resultssupporting
confidence: 80%
“…This structure cannot be upheld in a bulk crystal. In accordance with the TiO 2 -free reference Al 2 O 3 sample of ref , it is therefore concluded that all ALD-Al 2 O 3 -based films, i.e., pure films and monolayers sandwiched between SiO 2 , have only a tetrahedral O coordination. This is supported by molecular dynamics structure studies of amorphous Al 2 O 3 that calculated 85% 4-fold coordination (plus 13% 5-fold coordination) for densities of 3.0 g/cm 3 , a typical value for ALD-Al 2 O 3 deposited at elevated temperatures. , …”
Section: Resultssupporting
confidence: 80%
“…10,11 Especially Al2O3 / TiO2 nanolaminates have applications in optics, 10,19 because the Al2O3 is a low-refractive-index and the TiO2 a high-refractive-index material. 20 In mixed oxides 21 (Al2O3 and TiO2) and Al2O3 / TiO2 nanolaminates, 22 tailored optical properties varying from Al2O3 to TiO2 with gradual composition change have been demonstrated. Electrical properties 23,24 can be tuned by adjusting either the TiO2 fraction 25,26 or the bilayer thickness 27,28,29,30 or with an interfacial layers.…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…Figure 2e shows the X‐ray absorption near‐edge structure (XANES) of the oxygen K‐edge, which mainly presents TiO 2 peaks instead of those of ALD aAlO x . [ 23 ] ALD aAlO x usually contains OH groups and carbon–oxygen (CO) molecules, resulting in oxygen vacancies. [ 13a ] The annealing process enables the OH groups to escape.…”
Section: Resultsmentioning
confidence: 99%